2018
DOI: 10.3389/fpsyg.2018.01311
|View full text |Cite
|
Sign up to set email alerts
|

A Growth-Curve Analysis of the Effects of Future-Thought Priming on Insight and Analytical Problem-Solving

Abstract: Research based on construal level theory (CLT) suggests that thinking about the distant future can prime people to solve problems by insight (i.e., an “aha” moment) while thinking about the near future can prime them to solve problems analytically. In this study, we used a novel method to elucidate the time-course of temporal priming effects on creative problem solving. Specifically, we used growth-curve analysis (GCA) to examine the time-course of priming while participants solved a series of brief verbal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Finally, the results of this study showed college students' insight problem solving can be improved by priming and practice, this is partially consistent with the finding of previous research concerning the impact of future-thought priming on insight and analytic problem-solving (Slepian et al, 2010;Truelove-Hill et al, 2018). It is worth noting that different types of priming may generate different levels of impact on insight problem solving.…”
Section: Implications and Future Researchsupporting
confidence: 90%
“…Finally, the results of this study showed college students' insight problem solving can be improved by priming and practice, this is partially consistent with the finding of previous research concerning the impact of future-thought priming on insight and analytic problem-solving (Slepian et al, 2010;Truelove-Hill et al, 2018). It is worth noting that different types of priming may generate different levels of impact on insight problem solving.…”
Section: Implications and Future Researchsupporting
confidence: 90%
“…Indeed, numerous studies have highlighted the existence of associative priming phenomena in problem-solving, like the ones that govern word and sentence associations ( Hare and Goldberg, 2020 ). Overall, priming can have a significant impact on problem-solving ability, and the specific type of priming used can affect the problem-solving process ( Truelove-Hill et al, 2018 ). For example, priming has been shown to positively influence creative problem solving, with individuals in primed conditions demonstrating better performance than those in unprime conditions (e.g., Berger et al, 2021 ).…”
Section: Large Language Models (Llms)mentioning
confidence: 99%
“…It is striking that while Libet's experiments have been widely criticized from spheres that are not exactly neuroscientific, there have been few attempts to reproduce or refute them experimentally. In a recent series of experiments (Jung-Beeman et al, 2004;Truelove-Hill et al, 2018;Zhu et al, 2021), carried out with advanced recording techniques, the group led by J. Kounios has studied the brain activity related to the so-called "aha" moment (that is, the instant one feels accounts for the solution or explanation of a problem). The experimental subjects had to press a switch at the moment they found the solution to a word problem.…”
Section: Unconscious and Conscious Processing Carried Out By Neural C...mentioning
confidence: 99%